Dental Care Delivery in a Social Assistance Center in Mexico: A 14-Month Case Series of Children and Adolescents in Foster Care - Preciado-Meza, Guillermina (2026)
All children and adolescents have the right to receive a series of special protection and assistance measures from their respective countries. States must protect them from all forms of maltreatment, harm, neglect, or abuse. In cases that arise, the priorities must be the restoration of rights and residential care that provides comprehensive services including health. The paper reports a descriptive and retrospective study for a 14-month period conducted as a case series of 54 children and adolescents who received dental care in a Social Assistance Center in Mexico, where they were temporarily housed. Based on the initial clinical evaluations, it was identified that 100% of them had at least one untreated cavitated caries lesion, and 64.8% had apparently not received previous dental care. A total of 418 dental procedures were performed and 19 patients were discharged with completed treatment plans. There is a need to seek more collaborative approaches and to make positive contributions to improve the oral health of the pediatric population in situations of vulnerability and Foster Care.